Headset attentional synchrony: tracking the gaze of viewers watching narrative virtual reality. Issue 3 (3rd July 2019) - Bender, Stuart
ABSTRACT: Eyetracking studies of traditional movies have shown that although viewers are free to look at any part of a film or television clip, the gaze behaviours of viewers predominantly cluster around predictable features. This phenomenon is called attentional synchrony . Virtual Reality (VR) hype promises viewers to choose their own viewpoint on scenes regardless of directorial intention. This article is the first scholarly work to examine attentional synchrony in the so-called Cinematic VR. The study uses a hybrid creative-practice research model to test the extent to which attentional synchrony is achieved in two VR productions. The videos present the same dramatic narrative from two optical and narrative viewpoints: a 'first person' point of view and a 'third person' perspective. After testing on audiences using VR headsets, the results of the research show that attentional synchrony was achieved in both productions. The result is slightly stronger in the first person point of view production, and the expected difficulty of the increased editing pace in the third person point of view did not result in substantially lower levels of attentional synchrony. The article discusses practical and theoretical considerations of editing 360-degree VR in order to synthesise industry heuristics with testable hypotheses.